انحراف الشخصية بحث ميداني في قضاء المدائن لمدينة بغداد (Journal Of Educational and Psychological Researches, 2013)
This search modest deviation personal than to doubt that the event was not guilty by nature or offenders of evil in origin but is arictim of misfortune that makes him grow or live in the center of the corruption, even if he could be in the middle of the blessing of good and virtue and reform lived living righteousness and honor it was  a useful member for himself and his community and must state and family community take hands mnhrfaite in order to prevent and provide then